STRATEGI GURU PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK SIKAP DEMOKRATIS PESERTA DIDIK UNTUKMENINGKATKAN PARTISIPASI POLITIK (STUDI DI SEKOLAH MENENGAH ATAS NEGERI 1 SUMBERLAWANG SRAGEN) - Prasetyani, Nur?aini Dwi; Rejekiningsih, Triana; Yuliandari, Erna (Educitizen, 2017)
The objectives of research were to find out: (1) strategy the Civic Education teachers took in building democratic attitude among the students to improve political participation in SMA Negeri 1 Sumberlawang Sragen, (2)  students? perception on political participation in SMA Negeri 1 Sumberlawang Sragen,, and (3) factors supporting and inhibiting the Civic Education teachers in building democratic attitude among the students to improve political participation in SMA Negeri 1 Sumberlawang Sragen. This research employed qualitative research, with descriptive qualitative type. Data source derived from informant, place, event, and document. The sampling technique used was purposive sampling. Techniques of collecting data were interview, observation, and document analysis. Data validation was conducted using data and method triangulations. Data analysis was carried out using an interactive analysis model.Considering the result of research, the following conclusions could be drawn. (1) The strategies the Civic Education teacher took in building students? democratic participation to improve political participation were as follow: a) identifying the characteristics of students, b) developing Learning Implementation Plan supporting learning material and objective relevant to building the students? democratic attitude, c) applying student active learning, learning strategy case study, learning problem solving model, learning inquiry method, learning technique, and learning assessment concerning the material featuring the political participation of participants, d) applying democratic attitude counselling activity to the students in all of basic competencies in the learning process in the classroom, e) coordinating with the school management to build the students? democratic attitude out of Civic Education or other class hour,(2)The students? perception on democratic participation improved, for example:  understanding the importance of participation in political participation activity and ability of determining attitude when they were within society as good citizen. (3) enabling and inhibiting factors of the implementation of the strategy of teachers of Civics in shaping the democratic attitude of learners to improve political participation as follows: a) supporting factors, namely: (i) strategies teachers right and appropriate to the learning objectives, (ii) the support of the school, (iii) adequate learning facilities, (iv) the condition of learners who support teachers' implementation of the strategy; inhibiting factor is the internal factors of learners such as attitudes of students when the teacher explains, and internal factors are environmental factors. Keywords: Civic Education teacher, Democratic Attitude, Political Participation